(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Dyslipidemia is a major phenotype associated with diabetes mellitus, and this is essential in the development of cardiovascular risk. This study aimed to establish the most common dyslipidemia pattern among type 2 DM, atherogenicity, and associated insulin sensitivity. Across-sectional study, involving 141 type 2 diabetes patients and 140 healthy individuals as controls, was adopted. A multistage sampling technique was employed, and a semi-structured interviewer-administered questionnaire was used to collect socio-demographic and clinical data. The combined dyslipidemia pattern had the highest percentage among subjects, with a value of 52(45.6%) observed. It was followed by mixed dyslipidemias with a value of 50(43.9%). Ahigher percentage of increased risk of CVD was found among the subjects for CRI-I (74; 52%), CRI-II (73; 51.8%), and AC (75; 53.2%) compared with control CRI-I (15; 10.7%), CRI-II (7; 5.0%) and AC (15; 10.7%), p-values <0.001. A greater percentage of subjects demonstrated insulin resistance, as indicated by HOMA-IR (79, 56.0%) and QUICKI (64, 45.4%), compared to the controls with p <0.001. HbA1C correlated with HOMA-IR (r=0.235, p=0.005) and QUICKI (r=-0.196, p=0.020). Mixed dyslipidemias (elevated total cholesterol, elevated LDL-C and low HDL-C) as the highest form of dyslipidemia pattern was observed. CRI-I, CRI-II and AC were better predictors of CVD than an ordinary lipid profile. HOMA-IR and QUICKI were better tools for assessment of insulin sensitivity/resistance than plasma glucose and insulin. HbA1c can therefore be adopted as a screening tool for insulin resistance in a large population, not as a diagnostic tool alone.